Influência da arborização urbana nas ruas de Altamira-PA - TELES, Andrew Viana (2021)
The process of accelerated and disorganized urban growth has triggered a diversity of environmental impacts, having as reflexo, the occupation and anthropic activities on the environment, among which stands out the urban climate change. The objective of this work was to identify the different species used in afforestation, relating their climatic factors of temperature and relative humidity in the streets with and without afforestation in the urban area of Altamira-Pará. To collect the data, for the arboreal survey, an inventory was made in the wooded streets and for the microclimate survey was carried out with the help of the equipment Thermo-hygrometer AK28, data was obtained on temperature and relative humidity of the air in the hottest hours of the day, in various points in the streets with and without forestation. According to the tree survey, a total of 165 individuals were found distributed among 16 species and 7 families, and the Ipe species was the one with the highest number of individuals. For the microclimate variables, the air temperature values of the wooded streets contributed to the microclimate with a difference of 2.3ºC. Relative air humidity averaged 30% in wooded streets and 27% in nonwooded streets, a difference of 3%. Urban afforestation directly influences the improvement of temperature and relative humidity of the air, in this feeling, the planning of urban afforestation becomes indispensable to provide improvements in the microclimate ofthe city as well as a better quality of life for the population.